2008
DOI: 10.1111/j.1364-3703.2008.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and pathway for phloem‐dependent movement of Melon necrotic spot virus in melon plants

Abstract: The translocation of Melon necrotic spot virus (MNSV) within tissues of inoculated and systemically infected Cucumis melo L. 'Galia' was studied by tissue-printing and in situ hybridization techniques. The results were compatible with the phloem vascular components being used to spread MNSV systemically by the same assimilate transport route that runs from source to sink organs. Virus RNAs were shown to move from the inoculated cotyledon toward the hypocotyl and root system via the external phloem, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 85 publications
0
24
0
3
Order By: Relevance
“…Hybridization was performed with 500 ll hybridization solution (50% formamide, 6 9 SSC, 3% SDS, yeast tRNA 0.1 mg ml -1 ) as described by Gosalvez-Bernal et al (2008) and a DIG-labeled RNA probe complementary to positions 1418-2111 of ALSV-RNA2 (100 ng per slide) at 55°C for 20 h. Washing after hybridization was conducted as described by Takagi et al (2008). Hybridized probes were detected by sheep anti-DIG conjugated to alkaline phosphatase (Roche Plant Mol Biol (2011) 75:193-204 195 Molecular Biochemicals) diluted 1:500 in buffer 1 containing 0.2% Tween 20 for 30 min.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Hybridization was performed with 500 ll hybridization solution (50% formamide, 6 9 SSC, 3% SDS, yeast tRNA 0.1 mg ml -1 ) as described by Gosalvez-Bernal et al (2008) and a DIG-labeled RNA probe complementary to positions 1418-2111 of ALSV-RNA2 (100 ng per slide) at 55°C for 20 h. Washing after hybridization was conducted as described by Takagi et al (2008). Hybridized probes were detected by sheep anti-DIG conjugated to alkaline phosphatase (Roche Plant Mol Biol (2011) 75:193-204 195 Molecular Biochemicals) diluted 1:500 in buffer 1 containing 0.2% Tween 20 for 30 min.…”
Section: Rt-pcrmentioning
confidence: 99%
“…The sections were treated with proteinase K (1.5 lg/mL) and fixed in 4% (v/v) paraformaldehyde. Hybridization was performed as described by Gonsalvez-Bernal et al (2008) at 48°C for 30 h with 200 lL hybridization solution [50% (v/v) formamide, 69 SSC, 3% (w/v) SDS, 0.1 mg/mL yeast tRNA] and DIG-labeled RNA probes complementary to positions 1418-2111, 2111-2618, and 2619-3197 of ALSV-RNA2. After hybridization, washing was conducted as described by Takagi et al (2008).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Although results of previous studies indicated that the movement of phloemlimited viruses is restricted by vascular connectivity among leaves (Leisner et al 1992;Andrianifahanana et al 1997;Gosalvez-Bernal et al 2008), the movement of phytoplasmas, which are phloem-limited bacteria, does not appear to be limited by vascular architecture (Kuske and Kirkpatrick 1992;Constable et al 2003;Christensen et al 2004). Instead, phytoplasmas tend to accumulate in source leaves, perhaps because they attach to the sieve-element membrane, are retained in the sieve pores, or are self-mobile (Christensen et al 2004).…”
Section: Introductionmentioning
confidence: 98%